2001
DOI: 10.1152/ajpgi.2001.280.1.g139
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine expression of activated transforming growth factor-β1 induces apoptosis in normal rat liver

Abstract: The aim of this study was to determine the differential effects of latent and activated transforming growth factor (TGF)-beta(1) in growth control of normal and proliferating hepatocytes in vivo. Rats were injected with adenoviruses expressing control transgenes (Ctrl), latent TGF-beta(1) [TGF-beta(L)], or activated TGF-beta(1) [TGF-beta(A)]. Additional animals underwent two-thirds partial hepatectomy (PH) 24 h after injection. Increased hepatocyte apoptosis was observed in TGF-beta(A)-injected but not TGF-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…It has been suggested that the release of TGF-β1 from lacerated muscle can induce the pathological differentiation of marrow-derived stem cells and other types of muscle cells (Li et al 2004). The continued upregulation of TGF-β1, via an autocrine mechanism, not only contributed to the infiltration of lymphocytes, but also triggered muscle cells to differentiate into fibroblasts and underwent atrophy during muscle healing, and had effects in various other types of cells, including cardiomyocytes and hepatocytes (Taimor et al 1999;Schrum et al 2001). TGF-β1 can induce collagen deposition by increasing synthesis of most matrix proteins and decreasing the production of matrix degrading proteases via the p38 MAPK pathway (RodriguezBarbero et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the release of TGF-β1 from lacerated muscle can induce the pathological differentiation of marrow-derived stem cells and other types of muscle cells (Li et al 2004). The continued upregulation of TGF-β1, via an autocrine mechanism, not only contributed to the infiltration of lymphocytes, but also triggered muscle cells to differentiate into fibroblasts and underwent atrophy during muscle healing, and had effects in various other types of cells, including cardiomyocytes and hepatocytes (Taimor et al 1999;Schrum et al 2001). TGF-β1 can induce collagen deposition by increasing synthesis of most matrix proteins and decreasing the production of matrix degrading proteases via the p38 MAPK pathway (RodriguezBarbero et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This effectively results in enhanced cell proliferation and reduced cell death [55]. Livers in rats in which TGF-β is overexpressed and cell proliferation is inhibited cannot regenerate after partial hepatectomy [56], indicating that enhanced cell proliferation and reduced apoptosis is of high importance for liver regeneration. Another good example, demonstrating the coordinated control of cell numbers and organ size by cell proliferation and apoptosis, was shown in tumor-promoting agent treatment experiment in liver and kidney.…”
Section: Coordination Of Cell Proliferation and Cell Death In Size Comentioning
confidence: 99%
“…As described previously, caspase-3 and caspase-8 activities were determined with the substrates DETD-AFC and LEVD-AFC, respectively, by fluorometric analysis on a Perkin Elmer Luminescence Spectrometer LS50B (Perkin Elmer; Norwalk, CT) [3]. Hepatocytes were plated at a density of 1.5 × 10 6 in a 60 mm dish and lysed in a 1× lysis buffer (10 mM HEPES, 2 mM EDTA, 0.1% CHAPS, 5 mM DTT, 1 mM PMSF, 10 μg/ml pepstatin A, 10 μg/ml aprotinin, 20 μg/ml leupeptin) by five rapid freeze/thaw cycles.…”
Section: Caspase-3 and Caspase-8 Activitymentioning
confidence: 99%
“…After partial hepatectomy, TGFβ has an integral role in terminating liver regeneration secondary to its hepatocyte anti-proliferative effects. In vitro and in vivo studies have also shown that TGFβ controls hepatocyte growth directly by inducing apoptosis [2][3][4]. Furthermore, TGFβ-induced apoptosis occurs through ROS generation, the mitochondrial permeability transition (MPT), and caspase activation [5].…”
Section: Introductionmentioning
confidence: 99%